Clinical application of Ruiyun Procedure for Hemorrhoids combined with hemorrhoidectomy in rectal Intramucosal prolapse with mixed hemorrhoids - Zhu Lili; Luo Zhuang (结直肠肛门外科)
[Objectives] To evaluate the efficacy of Ruiyun procedure for hemorrhoids (RPH) combined with hemorrhoidectomy in the treatment of rectal intramucosal prolapse with mixed hemorrhoids. [Methods] A total of 60 patients with rectal intramucosal prolapse combined with mixed hemorrhoids treated in our hospital from November 2019 to November 2021 were recruited. They were randomly divided into the control group (treated with rectal mucosal point by point ligation combined with hemorrhoidectomy) and the observation group (treated with RPH combined with hemorrhoidectomy), with 30 cases in each group. The clinical efficacy, constipation symptom score, postoperative complications, and recurrence were compared between the two groups. [Results] The total efficacy rate was 100% in both groups. The curative effect of the observation group was better than that of the control group, and the cure rate was higher than that of the control group, the differences were statistically significant (P < 0.05). Before operation, there was no significant difference in constipation symptom scores between the two groups (P > 0.05). After operation, the constipation symptom score of the two groups was lower than that before operation, and the constipation symptom score of the observation group was lower than that of the control group, and the differences were statistically significant (P < 0.05). The total incidence of complications in the observation group was 10% (3/30), which was lower than 33.3% (10/30) in the control group, and the difference was statistically significant (P < 0.05). No patients were lost to follow-up for 1 year after operation. The recurrence rate in the observation group was 3.3% (1/30), which was 26.7% (8/30) in the control group. The difference between the two groups was statistically significant (P < 0.05). [Conclusion] RPH combined with hemorrhoidectomy for rectal intramucosal prolapse with mixed hemorrhoids is effective. Compared with rectal mucosal point by point ligation combined with hemorrhoidectomy, it can improve the cure rate, effectively improve postoperative constipation symptoms, reduce the total incidence of postoperative complications and recurrence, and has good clinical application value.